Customer satisfaction mediates the effect of product innovation and service quality on customer loyalty - Alsukri, Saipul; Miran, Ikas; Cakranegara, Pandu Adi; Prihastuti, Asepma Hygi (INOVASI, 2022)
This study aims to determine the effect of product innovation and service quality on customer satisfaction and customer loyalty at Honda motorcycle customers in Kampar Regency. Data collection was obtained through questionnaires collected from 105 consumers of Honda motorcycles in the Kampar Regency. The technique of sampling uses non-probability sampling and sample selection by purposive sampling. The data processing methods in this research are validity, reliability, the goodness of fit using Structural Equation Model (SEM) with Amos, and path analysis using the Sobel test. This study found that product innovation and service quality significantly affected customer satisfaction. Customer satisfaction has a significant effect on customer loyalty. Product innovation and service quality have no direct effect on customer loyalty. Product innovation and service quality significantly affect customer loyalty through customer satisfaction.